Once, Twice, Three Times Delayed: Considering A Permanent Stay of Prosecution in Rodrigues v The National Director of Public Prosecutions - Van der Linde, Delano Cole (Potchefstroom Electronic Law Journal, 2022)
The National Prosecuting Authority is vested with the power, as dominus litus, to institute and discontinue charges whereas high courts are empowered to order a permanent stay of the prosecution prohibiting the continuation of the trial. However, such an order is considered to be a "drastic remedy" and is not empowered in terms of statutes such as the Criminal Procedure Act 51 of 1977 but rather vested in the right of an accused to have their trial begin and conclude without unreasonable delay. A permanent stay of the prosecution is an order made on a case-by-case basis, balancing various factors such as the prejudice faced by the accused, systemic factors as well as the reason for the delay. The ultimate question however remains whether the lapse of time in a particular case is unreasonable. The Supreme Court of Appeal in Rodrigues v The National Director of Public Prosecutions had to evaluate whether the 47-year-delay and eventual prosecution between the death of anti-apartheid activist, Ahmed Timol, was unreasonable. Both the majority and minority of the Supreme Court of Appeal, although for different reasons, concluded that the delay was not unreasonable. For most of the 47 years, prosecuting the accused was not possible due to the surrounding historical and political reasons (including the moratorium of cases arising from the Truth and Reconciliation Commission). The National Prosecuting Authority, as soon as it was possible, initiated the prosecution of the accused. Although applications for a permanent stay are mostly viewed as prejudicial to the accused, the majority and minority both acknowledge the families of the victims in this case. Such a perspective is welcomed as the role of the victim in the criminal justice process is often neglected.